ANALISIS YURIDIS TERHADAP PENGAWASAN BANK INDONESIA DALAM KEGIATAN TRANSAKSI MATA UANG VIRTUAL ( VIRTUAL CURRENCY ) DI INDONESIA - Muhammad Hendra Razak; Bismar Nasution; Mahmul Siregar; Sunarmi Sunarmi (Universitas Sumatera Utara, 2018)
ABSTRACT This virtual currency developments give rise to legal issues in Indonesia, especially on legislation and related policies as well as currencies. The use of virtual currency as a means of payment is essentially at odds with the Article Number 7 year 1999 Of Currencies. In addition, because of the virtual currency is the currency that exists in the digital world of virtual currency, then it does not qualify as a currency. In General, institutions and or monetary authority in a country is submitted to a Central Bank. In Indonesia, the institutions and authorities in the field or authority is monetary Bank Indonesia in accordance with the mandate of article 10 Article Number 23 of the year 1999 On Bank Indonesia. As monetary authorities, banking and payment systems, the main task of the Bank Indonesia not only maintained the stability of the monetary, but also the stability of the financial system (banking and payment systems). This thesis raised issues about the role of Bank Indonesia in overseeing the monetary traffic in Indonesia, the rule of law which deals with money and other means of payment dikatikan with the legality of virtual currency (virtual currency) in Indonesia, the legality of payments by using virtual currency (Virtual Currency) in transactions using electronic media, and the role of Bank Indonesia as Indonesia's monetary authority in overseeing the traffic circulation virtual (virtual currency currency) in Indonesia. Based on the results of this research it can be concluded that the use of virtual currency in the activity or transaction and payment obligations that must be met with money on the territory of the unitary State of Republic of Indonesia is invalid (illegal) and is acts that violate the law, eyes virtual (virtual currency) has no legal basis or the legality to be used electronically transaction activity in the territory of a unitary State of Republic Indonesia, it is also in line with the Article Number 7 Year 2011 About currency, Article Number 23 of the year 1999 On Bank Indonesia, the supervision conducted by Bank Indonesia as well as the financial services authority, as well as agencies or other entities with an interest in the Country's monetary The unity of the Republic of Indonesia is not able to detect the activity of transactions carried out by the parties – parties users virtual currency (virtual currency) caused tertutupnya user access virtual currency (virtual currency) to Bank Indonesia as authority in the field of monetary authorities in Indonesia. Therefore, we suggest that the Government, through the agency or institution in the field of monetary authorities and financial services merivisi the rules of the currency by adding atuan prohibitions of the use of virtual currency in the Article number 7 of the year 2011 About The Currency. In addition, through the agency or agencies that are authorized to take and make decisions about its own rule making authority to block sites – sites of service providers selling – buy and the virtual currency or if its use is forbidden in the territory of a unitary State of Republic Indonesia. Keywords: Bank Indonesia, Virtual Currency